Guilt аs а sign of a subjective side of the violation of the rules of safety while fulfilling risky jobs - Крайник, Г. С. (Theory and practice of jurisprudence, 2016)
In the article author analyzed the guilt аs а sign of a subjective side of the violation of the rules of safety while fulfilling risky jobs (a. 272 of CC of Ukraine), mixed form of guilt etc.